2012
DOI: 10.1039/c2dt30521f
|View full text |Cite
|
Sign up to set email alerts
|

The anti-diabetic bis(maltolato)oxovanadium(iv) decreases lipid order while increasing insulin receptor localization in membrane microdomains

Abstract: The effects of treatment with bis(maltolato)oxovanadium(IV) (BMOV) on protein localization in membrane microdomains were investigated by comparing the effects of insulin and treatment with BMOV on the lateral motions and compartmentalization of individual insulin receptors (IR). In addition, effects of insulin and BMOV on the association of IR, phosphorylated IR (pIR) and phosphorylated insulin receptor substrate-1 (pIRS-1) with chemically-isolated plasma membrane microdomains on rat basophilic leukemia (RBL-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 123 publications
(248 reference statements)
2
42
0
1
Order By: Relevance
“…Chemical intuition might suggest that the HMet + should be penetrating the AOT interface because of chemical compatibility and Columbic attraction, and we have previously measured such an effect for other systems such as pyridine-2,6-dicarboxylic acid (dipic) [53] and metal complexes such as [VO 2 dipic] -and bis(maltolato)oxovanadium(IV) (BMOV). [20,25] NMR spectroscopic results show that the chemical shift for the HMet + methyl proton changes, which is consistent with penetration into the interface. The IR spectroscopic results show that HMet + ions significantly affect the hydrogen-bonding network present in the water pool.…”
Section: Ftir Studies Of Hmetv 10 In Rmssupporting
confidence: 76%
See 2 more Smart Citations
“…Chemical intuition might suggest that the HMet + should be penetrating the AOT interface because of chemical compatibility and Columbic attraction, and we have previously measured such an effect for other systems such as pyridine-2,6-dicarboxylic acid (dipic) [53] and metal complexes such as [VO 2 dipic] -and bis(maltolato)oxovanadium(IV) (BMOV). [20,25] NMR spectroscopic results show that the chemical shift for the HMet + methyl proton changes, which is consistent with penetration into the interface. The IR spectroscopic results show that HMet + ions significantly affect the hydrogen-bonding network present in the water pool.…”
Section: Ftir Studies Of Hmetv 10 In Rmssupporting
confidence: 76%
“…How vanadium compounds are transported in biological systems is a complex topic that has been investigated by focusing both on transport by proteins in the blood as well as transport across membranes. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]28,35] The complexity of this topic is exacerbated by the aqueous oxovanadate chemistry because multiple species, nuclearities, and protonation states exist under physiological conditions. The interaction of V 10 with interfaces has been investigated in cells as well as in simple model systems such as reverse micelles (RMs) prepared from an organic solvent, water, and a surfactant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, their potential insulin mimetic capacity has been extensively investigated [10][11][12][13][14][15][16]. It has been shown that VCs can be used to mitigate insufficient insulin response in DM thus presenting insulin-mimetic properties in vitro and [17][18][19][20] in vivo [21][22][23][24], and two of them were tested in clinical trials [25]. To date, the main limitation for the clinical use of VCs in the treatment of diabetes has been their potential toxicity [26].…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23] Among the several complexes exhibiting insulin enhancing properties, V IV O(maltolato) 2 (BMOV) and V IV O(ethylmaltolato) 2 (BEOV) have been extensively studied from the chemical and pharmacological points of view. 8,[21][22][23][24][25][26] Complexes with 3-hydroxy-4-pyrones (3,4-HP) have also been extensively studied. 19,[24][25][26][27][28][29] Replacement of the O atom of the pyrone ring by a N or N-R group yields pyridinone derivatives, and both families of compounds maintain the (O − , O − ) binding set, forming quite stable complexes with many metal ions.…”
Section: Introductionmentioning
confidence: 99%